The display makes a difference: A mobile eye tracking study on the perception of art before and after a museum's rearrangement - Luise Reitstätter; Hanna Brinkmann; Thiago Santini; Eva Specker; Zoya Dare; Flora Bakondi; Anna Miscená; Enkelejda Kasneci; Helmut Leder; Raphael Rosenberg (Bern Open Publishing, 2020)
There is increasing awareness that the perception of art is affected by the way it is presented. In 2018, the Austrian Gallery Belvedere redisplayed its permanent collection. Our multi-disciplinary team seized this opportunity to investigate the viewing behavior of specific artworks both before and after the museum's rearrangement. In contrast to previous mobile eye tracking (MET) studies in museums, this study benefits from the comparison of two realistic display conditions (without any research interference), an unconstrained study design (working with regular museum visitors), and a large data sample (comprising 259 participants). We employed a mixed-method approach that combined mobile eye tracking, subjective mapping (a drawing task in conjunction with an open interview), and a questionnaire in order to relate gaze patterns to processes of meaning-making. Our results show that the new display made a difference in that it 1) generally increased the viewing times of the artworks; 2) clearly extended the reading times of labels; and 3) deepened visitors' engagement with the artworks in their exhibition reflections. In contrast, interest in specific artworks and art form preferences proved to be robust and independent of presentation modes.